The Influence of the Supervision Function, Human Resource Development and the Utilization of Information Technology on Performance (Case Study) - Afandi, Irfan; Syahrir, Syahrir (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to determine the effect of the Influence of Oversight Function, Human Resource Development and Utilization of Information Technology on Performance (Case Study of Village Office Staff in Libureng District, Bone Regency). This study uses a quantitative approach. The sampling method used in this research is saturated sample or taking the entire population with 80 samples of respondents. The results of this study indicate that partially the function of supervision and development of human resources has a positive and significant effect on performance, and the use of information technology does not have a positive effect on the performance of village office staff in Libureng sub-district, Bone Regency.